REDESAIN LOGO VOLUMINA DI JANJI DESIGN LAB - Wiliandika, I Made Sapta; Artawan, Cokorda Alit; Wirawan, I Gusti Ngurah (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
The MBKM internship/work practice program organized by ISI Denpasar is an opportunity given to students, especially from the DKV study program, to try and explore visual design in the business/industrial world. The issue raised in this article is the redesign of the Volumina logo, which is brand audio visual services. The problem faced by Volumina is that the logo does not yet give a strong impression of a brand which focuses on audio visuals. One of the studios that provides services branding, especially logo design, namely Janji Design Lab, which is located at Taman Muding Mekar Housing Complex, Blok D No. 27B, Kerobokan, North Kuta, Badung, Bali. During the MBKM internship/work practice activities, the author received several projects related to visual communication design, such as photography, social media content design, motion graphic, and redesigning a logo brand, namely Volumina which focuses on the audio visual services sector. The method used in redesigning the Volumina logo was qualitative descriptive research by observing visual data owned by Volumina and interviews with owner Volume. The next detailed stage is creating a mind map, moodboard, visual keyword, and applying the logo to the media using its mockup. All these stages were carried out in order to create a new Volumina logo that gives a strong impression as brand audio visual services and achieving marketing strategies to the audience.